Essays on sovereign debt - Wang, Zilong (2016)
This thesis analyzes various issues of sovereign debt from both theoretical and empirical perspectives. The first chapter investigates how global and country-specific factors like US interest rates, global risk aversion and the country-specific macroeconomic climate drive the dynamics of sovereign spreads in emerging countries. I develop a theoretical framework that pinpoints the determination of the equilibrium debt level, probability of default and sovereign spread, and test empirical implications derived from the predictions of the model. The chapter then employs a Structural Vector Autoregression (SVAR) model to show empirically how the spread of sovereign debt is influenced over time by the factors given above. The empirical results show that most of the variations in sovereign spreads are caused by global shocks such as the term structure of US interest rates and the global risk aversion. The findings also indicate that shocks from the US have a direct effect on sovereign spread and an indirect effect via country-specific macroeconomic fundamentals. Finally, the evidence produced validates the presence of some response patterns of sovereign spread to the global shocks.